STRATEGI PENGEMBANGAN TOKO KUE RUMAHAN “SISTERKITCHEN” MENGGUNAKAN ANALISIS SWOT DAN METODE BUSINESS MODEL CANVAS - Juliana, Ditha Putri; Sumawidjaja, Riyandi Nur (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to analyze the business development strategy of the home bakery "SisterKitchen" using the Business Model Canvas (BMC) approach supported by a SWOT analysis. The analysis reveals that the primary customer segments include individuals, resellers, and online buyers. The value propositions offered are fresh, preservative-free cakes, custom designs, and competitive prices. Social media serves as the main sales channel, supported by customer relationships strengthened through loyalty programs and testimonials. Key activities involve cake production, recipe innovation, and active promotion. Strategic partnerships with raw material suppliers, delivery services, and influencers play a crucial role in supporting operations. Revenue is generated from custom cake sales, snack boxes, and partnerships with resellers. Efficiency in resource management and cost structure is key to business sustainability. With a well-directed development roadmap, "SisterKitchen" has the potential to enhance its competitiveness and achieve sustainable growth.